PENGGUNAAN Bacillus spp. SEBAGAI AGENS BIOKONTROL UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN CABAI - Khaeruni, Andi; Gusnawaty, HS (Jurnal Agroteknos, 2012)
The use of Bacillus spp. Bacteria as biocontrol agents is one alternative disease control for Fusarium wilt Fusarium oxysporum f.sp. Lycopersici on chilli plant . this study aimed to determine the effectiveness of Bacillus spp. As a biocontrol agent in various ways of application to control Fusarium wilt disease in pepper in in-vivo. Experiments were prepared using two factor factorial in a completely randomized design (CRD). Factor 1 (Applications) consisted of levels, namely: application of biocontrol agent Bacillus spp. M11 isolates (B1), application of biocontrol agents Bacillus spp. isolates F133 (B2), and application biocontrol agent Bacillus spp. mix. M11 isolates and isolates F133 (B3). The second factor (time of inoculation/application) consisted 3 levels, namely: inoculating the seed (S1), inoculation of Bacillus spp. simultaneously with pathogen inoculation (S2), inoculation of Bacillus spp. one week after pathogen inoculation (S3), to see the effect of the two isolates of Bacillus spp. that the latent period, the biocontrol agents Bacillus spp. mix isolates M11 and F133, was the best treatment with the longest latency period of the disease (16 hsi), the best plant growth by plant height reached 57,39 cm, and the lowest disease incidence and severity were 12,96 % and 11,11 %, respectively interaction between agent Bacillus spp. mix. Isolates M11 and F133 at the time of application on seed significantly affected the incidence of disease and plat height. Keyword: biocontrol agents, Bacillus spp., and Fusarium oxysporum f.sp. Lycopersici